Comparative study of multiaxial fatigue methods applied to welded joints in marine structures - P.S. van Lieshout; J.H. den Besten; M.L. Kaminski (Fracture and Structural Integrity)
Marine structures are particularly prone to action of waves, winds and currents with stochastically varying composition, intensities and directions. Therefore, resultant stresses may cause multiaxial fatigue in specific welded structural details. For the assessment of multiaxial fatigue in welded joints, a wide variety of methods have been suggested. However, there is still no consensus on a method which can correctly account for non-proportional and variable amplitude loading. This paper beholds a comparative study of multiaxial fatigue methods applicable for design of marine structures. For the purpose of comparison several load cases were defined including non-proportional and variable amplitude loadings with different normal and shear stress amplitude ratios. Three types of methods are compared: those described by three different codes (i.e. Eurocode 3, IIW and DNV-GL), those described by three different multiaxial fatigue approaches from literature (i.e. Modified Carpinteri-Spagnoli Criterion, Modified Wohler Curve Method and Effective Equivalent Stress Hypothesis) and an approach based on Path-Dependent-Maximum-Range multiaxial cycle counting. From this study it has been concluded that non-proportional variable amplitude loading has a significant negative impact on the fatigue lifetime estimates, and that further research and experimental testing are essential to come to a consensus.